A new triterpenoid glycoside from the leaves and stems of Duranta repens. Issue 2 (17th January 2016) - Furusawa, Chisato; Yasuda, Shin; Tsuji, Hiroshi; Ito, Show; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi; Nohara, Toshihiro; Ono, Masateru
Abstract : A new triterpenoid glycoside (1 ) was isolated from the methanol extract of the leaves and stems of Duranta repens L. (Verbenaceae) along with 14 known compounds consisting of eight triterpenoids, four iridoids, one phenylethanoid glycoside and one flavonoid. The chemical structure of1 was determined to be bayogenin 3- O -[β-D -glucopyranoside]-28- O -[α-L -rhamnopyranosyl-(1→5)- O -β-D -apiofuranosyl-(1→4)- O -α-L -rhamnopyranosyl-(1→2)- O -α-L -arabinopyranosyl] ester, based on spectroscopic data. In addition, the inhibitory effects of the isolates on lipoxygenase activity were examined. Among them, acteoside and apigenin resulted in 94 ± 3.6% and 82 ± 4.7% inhibition, respectively, at 0.5 mM. Abstract :